Nontuberculous mycobacteria in a tertiary Hospital in Portugal: a clinical review - Ruas, R (2017)
Background: Nontuberculous mycobacteria (NTM) form a heterogeneous group regarding their ability to cause disease. To further understand their clinical relevance, the characteristics of patients who had positive cultures for NTM at a tertiary hospital in Portugal were reviewed. Methods: Retrospective analysis of patients assessed at the Infectious Diseases (ID) Department of the São João Hospital Center, from January 2007 to December 2014, from whom at least one biological sample was tested culture positive for NTM. Results: A total of 74 patients with at least one positive culture for NTM were identified. Forty-nine (66.2%) were infected by the human immunodeficiency virus, 4 (5.4%) had cancer, and 7 (9.5%) were under immunosuppressive medication. A total of 13 patients (17.6%) fulfilled the American Thoracic Society/ID Society of America criteria for pulmonary NTM disease and treatment was initiated in 12 other patients (16.2%), all of which were immunocompromised. Mycobacterium avium complex was more frequently associated with disease, responsible for 56% of the patients treated. Patients were treated with antituberculosis drugs adjusted for the species isolated, and cure was achieved in 13 patients (52%). Conclusion: The present study highlights the importance of understanding the epidemiology of NTM to better comprehend their clinical impact.